The Influence of Accounting Information on the Success of Micro, Small and Medium Enterprises in Biletepung Hamlet, Beleka Village, District. Gerung West Lombok, West Nusa Tenggara - Yuliartika, Dina; Mawaddah, Nur Aulia; Silvi, Baiq; Yasa, I Putu Buda; Sari, Ni Kadek Wahyuni Merta (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Accounting information is a system commonly used by entrepreneurs to manage finances in running their business. Business owners, whether large, medium or small, are expected to be able to implement an accounting information system in managing their business. This will really help business owners to manage income and earnings in their business. Not only that, with an accounting information system, business owners can find out whether their business is experiencing a profit or loss. Usually, companies that implement an accounting system in managing their business will understand and understand where the costs or budget obtained or spent are used. So in this case the use of accounting information has a big influence on the progress of a business because with accounting information it can make it easier for entrepreneurs to manage the finances of the business they run.